Characterizing the Flowering Phenology of Rosa rugosa Thunb. as an Ecosystem Service in the Context of Climate Change in Kupinovo (Vojvodina), Serbia - Mirjana Ljubojević; Jelena Čukanović; Sara Đorđević; Djurdja Petrov; Nevenka Galečić; Dejan Skočajić; Mirjana Ocokoljić (Plants, 2025)
Given the growing impact of climate change, this study examines the flowering phenology of Rosa rugosa Thunb. in Kupinovo (Vojvodina, Serbia). Data collected over 18 years (2007–2024) were analyzed to assess changes in primary flowering, while secondary flowering was monitored from 2022 to 2025. Phenological stages were recorded every other day, and dates were converted into day-of-year (DOY) values. Heat accumulation (GDD) was calculated using daily max/min temperatures and thresholds. In 2024, R. rugosa exhibited a 37-day earlier onset and a 50.4-day later completion of primary flowering compared to previous years. The variability of key phenological events of primary flowering was observed in the interaction with climatic parameters, with regular fruiting. The species proved tolerant to heat and drought, suggesting potential range expansion. Optimal temperatures for secondary flowering were identified: abundant flowering occurred at 13.6 °C max and 4.9 °C min, while moderate flowering occurred at 9.0 °C max and 4.2 °C min. Regression analysis confirmed the positive effect of rising temperatures on flowering intensity. While freezing halted secondary flowering and damaged open buds, unopened buds remained unaffected. These findings highlight R. rugosa as a resilient, ornamental species, relevant to climate adaptation strategies, nature-based solutions, and the preservation of ecosystem services under global warming scenarios.